Respiratory Syncytial Virus: A Systematic Review and Meta-Analysis of Tomographic Findings (2000-2022) - Matteo Riccò; Silvia Corrado; Sara Palmieri; Federico Marchesi (MDPI AG, 2023)
Human respiratory syncytial virus (RSV) is a main cause of medical referrals and hospitalizations in all infants, particularly among newborns. Nevertheless, relatively limited evidence on chest tomography (CT) findings has been collected. According to the PRISMA statement, Pubmed, Embase, and medRxiv were searched for eligible observational studies published up to 31 December 2022. Cases were categorized in children and adolescents (age < 18 years), adults and elderly (age ≥ 18 years), and immunocompromised patients, and then pooled in a random-effects model. Heterogeneity was assessed using the I2 statistics, while reporting bias was assessed by means of funnel plots and regression analysis. A total of 10 studies (217 RSV cases) were retrieved (children, 37.3%; immunocompromised, 41.0%; adults, 21.7%). The most common features were signs of organizing pneumonia (33.65%, 95% confidence interval [95% CI] 22.39-47.27), followed by septal thickening (33.19%, 95% CI 21.76-47.03), ground glass opacities (GGOs; 28.03%, 95% CI 14.69-46.82), and tree-in-bud (TIB, 27.44%, 95% CI 15.04-44.68). Interestingly, up to 16.23% (95% CI 8.17-29.69) showed normal findings, while the large majority (76.06%, 95% CI 64.81-84.56) were characterized by bilateral involvement. Studies were highly heterogeneous without substantial reporting bias. Assuming children and adolescents as reference groups, healthy adults were characterized by a higher risk ratio [RR] for septal thickening (RR 3.878, 95% CI 1.253-12.000), nodular lesions (RR 20.197, 95% CI 1.286-317.082), and GGOs (RR 2.121, 95% CI 1.121-4.013). RSV cases are rarely assessed in terms of CT characteristics. Our study identified some specificities, suggesting that RSV infections evolve heterogeneous CT features in children/adolescents and adults, but the paucity of studies recommends a cautious appraisal.